Sulfur affects root growth and improves nitrogen recovery and internal efficiency in wheat. (28th May 2017) - Carciochi, Walter D.; Divito, Guillermo A.; Fernández, Lucrecia A.; Echeverría, Hernán E.
ABSTRACT: Wheat plants were cultivated in pots with the objective of evaluating the effect of two sulfur (S) rates (+S and −S) on (i) shoot growth, S and nitrogen (N) uptake and nitrogen use efficiency (NUE) and (ii) root growth and architecture and its relations with S and N uptake. Plant samplings were at Z39, Z51 and Z92 stages. Shoot mass and NUE were greater in +S treatment at the three stages. −S treatment increased root growth at Z39 (14% more length and 16% more tips) in comparison with +S, but the opposite occurred at Z51 (31% less area and 42% less mass). S uptake per unit root mass, area and length were greater in +S treatment at Z39 and Z51. A similar pattern was determined for nitrogen uptake (Nu) at Z39, but the opposite occurred at Z51. This indicates that Nu is mainly controlled by shoot growth and not by root growth.